Efektivitas Model Pembelajaran Discovery Learning Berbasis Science Technology Engineering Mathematics (STEM) Terhadap Kemampuan Kreativitas Matematis Siswa - Sulistianingsih, Diah Ayu; Yuliardi, Ricki (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to explore and measure the effectiveness of the Discovery Learning learning model based on Science Technology Engineering and Mathematics (STEM) on students' mathematical creativity abilities in mathematics subjects in class VII of SMPN 1 Kadugede. This research uses quantitative research with an experimental approach, specifically using the Quasi Experimental Design (quasi-experiment). The research design applied is nonequivalent pretest-posttest control group design. This study adopts a Quasi Experiment design, where two class groups are the subjects of the study. In selecting samples, this study used purvosive sampling technique: Class VII-G as the experimental class and VII-F as the control class, with each class having a total of 36 students. The experimental class uses the Discovery Learning model based on Science Technology Engineering and Mathematics (STEM), while the control class follows conventional learning methods. Student learning outcome data were collected through pretest and posttest. The data collection techniques used in this study were tests and questionnaires. The data analysis technique used the t-test. The results of this study indicate that the Discovery Learning model based on Science Technology Engineering and Mathematics (STEM) can improve students' mathematical creativity abilities